O contributo da Estratégia Nacional para o Mar 2013-2020 para a Política do Mar em Portugal - Gomes, Teresa Gardner Marques (2020)
The importance of the Atlantic Ocean both as a source of resources and opportunities at economic and geostrategic levels for Portugal has been widely recognized. The aim of the present work was to analyze and discuss the contribution of the Portuguese “National Ocean Strategy 2013-2020” for the Portuguese sea policy. The first section of present study reviewed chronologically the evolution of sea policy in Portugal. In the second section an in-depth analysis of the Portuguese “National Ocean Strategy 2013-2020” which includes its structure, monitoring and revision, was carried out. Moreover, an in-depth analysis of its action plan, “Mar-Portugal Plan” was made. The main conclusions drawn are the following: there was a limited capacity to take advantage of the motivation generated by EXPO 98 (Lisbon World Exhibition with the theme “The oceans: a heritage for the future”) and the initiatives it triggered; there has been a lack of coherence between structures and commissions that are being established and political decisions; and lack of continuity in terms of functions and strategies determined by those same structures and commissions. It is suggested that within what could be as a national plan, Portugal has not yet considered the sea as a main aim. However, I expect that this purpose will be achieved if Portugal continues to adopt coherent and deliberate policies.